Therapeutic Bacteriophages for Gram-Negative Bacterial Infections in Animals and Humans - Panagiotis Zagaliotis; Jordyn Michalik-Provasek; Jason Gill; Thomas Walsh (Case Western Reserve University, 2022)
Drug-resistant Gram-negative bacterial pathogens are an increasingly serious health threat causing worldwide nosocomial infections with high morbidity and mortality. Of these, the most prevalent and severe are Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli, Acinetobacter baumannii, and Salmonella typhimurium. The extended use of antibiotics has led to the emergence of multidrug resistance in these bacteria. Drug-inactivating enzymes produced by these bacteria, as well as other resistance mechanisms, render drugs ineffective and make treatment of such infections more difficult and complicated. This makes the development of novel antimicrobial agents an urgent necessity. Bacteriophages, which are bacteria-killing viruses first discovered in 1915, have been used as therapeutic antimicrobials in the past, but their use was abandoned due to the widespread availability of antibiotics in the 20th century. The emergence, however, of drug-resistant pathogens has re-affirmed the need for bacteriophages as therapeutic strategies. This review describes the use of bacteriophages as novel agents to combat this rapidly emerging public health crisis by comprehensively enumerating and discussing the innovative use of bacteriophages in both animal models and in patients infected by Gram-negative bacteria.